2022-RA-1439-ESGO Is it time to perform radiochemotherapy and brachytherapy for cervical tumors higher than 3 cm?. (20th October 2022) - Cordoba, Abel; Serouart, Benjamin; Bogart, Emilie; Deley, Marie Cécile Le; Gomez, Carlos Martinez; Leblanc, Eric; Hudry, Delphine; Escande, Alexandre; Tinier, Florence Le; Pasquesoone, Camille; Taieb, Sophie; Narducci, Fabrice
Abstract : Introduction/Background: The objective of this study is to evaluate the survival and describe the recurrence of patients with early stage cervical cancer treated with 'Schautheim radical hysterectomy' by minimally invasive surgery (MIS) at the Oscar Lambret Center. Methodology: From 01/1999 to 12/2018, we included all patients managed by minimally invasive surgery at the Oscar Lambret Center for early stage cervical cancer with tumor size < 4 cm (FIGO stage IA1 with emboli at IIA1). The primary endpoint was the 5-year overall and recurrence-free survival rates in these patients. Overall survival (OS) and Disease-Free Survival (DFS) were estimated from the initial biopsy using the Kaplan-Meier method. Hazard ratio (HR) was estimated with 95% confidence interval (CI95%). Results: A total of 239 patients were included. All patients underwent bilateral pelvic lymphadenectomy before radical hysterectomy . Preoperative image adapted brachytherapy (IABT) was performed in 125 patients. The 5-year overall and recurrence-free survival rates were 92% (95% CI 87.4–95%) and 86.9% (95% CI 81.6–90.7%), respectively. The multivariate analysis showed 2 associated factors to risk of recurrence: previous conization (HR = 0.21 (CI95% 0.06–0.70); p=0.01) and tumor size > 30 mm (HR = 2.26 (CI95% 1.08–4.73); p=0.031). We observed 33 recurrences, including 22 deaths due to disease. The recurrence rates were respectively 7.5% for tumor ≤20 mm, 12.9% for tumor between 20–30 mm, and 24.1% for tumor >30 mm. Conclusion: MIS is safe and for tumor size ≤20 mm with a very low rate of local recurrence; for tumors size >30 mm relapse rates are high and should be treated with concomitant radiochemotherapy and brachytherapy. For sizes between 20 and 30 mm, further data are needed to define management recommendations. Previous conization allow us to have a better accuracy regarding the tumor size in order to tailor the treatment.